PERAN GEGANA KORPS BRIMOB POLRI DALAM PENANGGULANGAN TINDAK PIDANA TERORISME - Wiridin, Darmawan; I Gede Arya, Arimbawa (Fakultas Hukum Universitas Dayanu Ikhsanuddin, 2025)
This study aims to determine the role of the Gegana Corps Brirnob Polri in countering terrorist crimes. To determine the standard operating procedures for countering terrorist crimes by Gegana Corps Brirnob Polri This study is a normative legal research using a statutory approach, a conceptual approach, a historical approach, and a philosophical approach. The results of this study conclude that the Role and Function of the Gegana Detachment of the Brimob Unit in Countering Terrorism Terrorist crimes are generally carried out by clandestine elements (underground networks) that are organized and specially trained. Security measures are carried out on team members before carrying out terrorist acts. Usually they are made into a cell system before carrying out the destruction of targets. Surveillance of terror targets is carried out by personnel who are specifically tasked as scouts. The crime of terrorism is regulated in Law Number 15 of 2003 concerning the Stipulation of Government Regulation in Lieu of Law Number 1 of 2002 concerning the Eradication of Criminal Acts of Terrorism into Law (Terrorism Law).The Terrorism Law was enacted at the time due to a pressing need, namely a series of bombings in the Republic of Indonesia, such as the Bali bombing and the Marriott bombing in 2003. These incidents had caused widespread public fear, resulting in loss of life and property damage, thus negatively impacting Indonesia's social, economic, and political life, and international relations. These bombings are a common tactic used by terrorists in several countries.